ANALISIS PREFERENSI SUMBER PERMODALAN PADA SENTRA INDUSTRI (STUDI KASUS SENTRA INDUSTRI KERAMIK DINOYO KOTA MALANG) - Rizki, Ramadhan Rahmat (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to: a. Analyzing and identifying problems in the capital sentra ceramic industry Dinoyo; b. Analyze and formulate solutions to overcome the problems of capital sentra ceramic industry Dinoyo. The method used in this study is qualitative. The results showed: the majority of informants are many who use their own capitalization, both the capital of the savings and loan capital from relatives, while in terms of capital many informants are reluctant to borrow from financial institutions because of fear of the condition and the existing mechanisms. Recommendations from the study of financial institutions must mengandeng ceramic business owners with the terms and mechanism that allows business owners to develop their business.Â Keyword: Sentra Ceramic Industry Dinoyo, Capital, Financial Institutions